Peningkatan Kompetensi Supply Chain Management Mahasiswa melalui Pelatihan Software POM-QM for Windows - Belia Afifah; Zulfikar Zulfikar; Siti Dinar Rezki Ramadhani; Dwila Sempi Yusiani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
In the midst of escalating industrial complexity in the digital era, the optimization of Supply Chain Management (SCM) becomes a key determinant of operational efficiency. However, a significant gap exists between students' theoretical understanding and practical mastery of decision-support software. This limitation in computational tool literacy potentially hinders graduates' competitiveness in the global job market. This community service activity aims to escalate students' technical skills through a webinar titled “UNLOCK YOUR SCM SKILLS: Forecasting, MRP, Transport - All in One Using POM QM” held on November 29, 2025. The implementation method was conducted online, encompassing comprehensive material dissemination and interactive questionnaire-based evaluation. The training focused on practical problem-solving in transportation using North West Corner and Least Cost methods, as well as the integration of Forecasting and Material Requirement Planning (MRP) modules. The service outcome demonstrated active participation from 84 participants affiliated with Universitas Maritim Raja Ali Haji (UMRAH), Politeknik Kampar, and Institut Teknologi Perkebunan Pelalawan Indonesia (ITP2I). Quantitative evaluation revealed a highly significant relevance of the material with an average score of 4.52 out of 5.00. Participants confirmed that mastering POM-QM software is highly applicable in supporting academic tasks, internship report preparation, and professional readiness. Overall, this activity effectively mitigates the competency discrepancy between SCM theory and practical implementation among students.